Manajemen Pengawasan Berbasis Islam - Risal Qori Amarullah; Kaimudin (STIT Sirojul Falah Bogor, 2024)
A good educational institution must be managed well. One form of management that must be owned by an educational institution is supervisory management. This serves to control the performance of personnel in an institution. However, due to human limitations as leaders who are entrusted with carrying out supervision, sometimes the guidelines and nature of supervision are separated. In this case, Islam answers the question; Islam teaches and gives instructions regarding supervision. In this paper, we will discuss Islamic-based supervisory management. This research contains 0 types of library research, namely activities to study something whose research is not only from one document but also seeks other sources that support the in-depth research that scientists conduct. According to the findings of this study, supervision in Islam is a control that is intended to maintain benefit and avoid damage and has characteristics such as being material and spiritual, monitoring, and employing humane methods that uphold human dignity. In Islam, the purpose of supervising is to control and correct someone to prevent them from falling into something that is wrong. This is in accordance with the principles of supervisory management in Islam, which consist of three points, namely: tawaşawbil aqqi (advising each other on the basis of truth and clear norms), tawaşaw bis şabri (advising each other on the basis of patience), and tawaşawbil marhamah (advising each other on the basis of affection).